Emergence of XIII.2.2 genotype of Avian Avulavirus-1 with unique FPCS site in India - N SARIKA; J JOHN KIRUBAHARAN; M VIDHYA; P SHILPA; RANJANI RAJASEKARAN (Indian Journal of Animal Sciences, 2022)
In the present study, two isolates namely D162 and D165 obtained from Newcastle disease outbreaks in backyard poultry in Tamil Nadu were subjected to phylogenetic analysis using complete Fusion (F) gene sequence to understand the circulation and evolution of Avian Avulavius-1 (AAv1). Further, these isolates were pathotyped based on mean death time and intra-cerebral pathogenicity index. Pathotyping and genotyping of D162 and D165 showed that these isolates belonged to velogenic pathotype and XIII.2.2 sub-genotype. In addition to this, the Fusion Protein Cleavage Site (FPCS) of F gene was analysed for amino acid sequence pattern. The amino acid sequence of FPCS of both D162 and D165 was 112RRRKRF117, which is unique among XIII.2.2 genotypes of AAv1, whereas it is common among Pigeon Paramyxovirus. It was hypothesized that cross-species infection by AAv1 has led to emergence of isolates with increased virulence.